An Interview with Peter Handke - June Schlueter (Studies in 20th & 21st Century Literature, 1979)
Handke comments on the relationship of his early essays to his fiction, maintaining that there is no theory of literature but only practice. For him, fiction brings daily occurrences into a new order, with the point of intersection of these occurrences suggesting a story. Handke believes there will always be a need for narrative prose which goes beyond mere reportage, and, with respect to his journal, Das Gewicht der Welt, he sees no contradiction between «journal» and «fiction.» His distinction between everyday and poetic language is central to Handke's approach to fiction. Explaining that there is no language for nature, he speaks at length of his latest novel, Langsame Heimkehr, which he calls an epic poem. Handke also comments on writers who have influenced his thinking and work, including Barthes and Hölderlin; considers the relationship of the creative impulse to film-making, drama, and fiction; and speculates as to why college students in America are attracted to his work.
Keywords: Peter Handke; narrative prose; Das Gewicht der Welt; journal; fiction; Langsame Heimkehr; epic poem; interview; Barthes; Hölderlin; film-making; drama